Nominal Convergence – Are We Getting Closer? - Otilia Georgiana Floroiu (Ovidius University Annals: Economic Sciences Series, 2020)
All countries that joined the European Union are obligated to adopt the euro currency, except for Denmark that benefits from an opt-out clause. Presently, there are eight EU Member states that are not part of the euro zone: Bulgaria, Croatia, Czechia, Denmark, Hungary, Poland, Romania, and Sweden. The national authorities are free to choose the time of accession and this prerogative allows some states to postpone by not entering the ERM II mechanism. But there are also countries who are severely struggling to meet the economic convergence levels. The degree of economic convergence is analyzed by the European Commission through Flash Eurobarometer surveys every two years. The purpose of this paper is to compare the 2018 Eurobarometer results with our own findings from December 2019, for a total of four countries: Romania, Poland, Hungary, and the Czech Republic.